The population structure of human carriage and clinical isolates of ESBL-producing Escherichia coli and Klebsiella pneumoniae in Norway - Andreassen, Lotte (UiT Norges arktiske universitet, 2017)
The increasing emergence of antimicrobial resistant bacteria worldwide is recognised as a severe threat to public health on a global scale. Without effective antimicrobial agents to treat bacterial infections, modern medicine will be set back several decades and deaths caused by bacterial infections will increase. The most widely used class of antimicrobials, is -lactams, and the increase in resistance against β-lactams due to -lactamases, and especially extended-spectrum -lactamases (ESBL) is a great concern. In this study, our aims were to determine the carriage rate of ESBL-producing E. coli and K. pneumoniae in a random population, and to investigate the population structure of ESBL-producing E. coli and K. pneumoniae isolates from both carriage- and clinical samples. The carriage isolates were obtained by screening of fecal samples from inhabitants in the Tromsø municipality, collected through the Tromsø-7 population study, and the clinical isolates were obtained from the 2014 NORM collection of ESBL-producing E. coli and K. pneumoniae, isolated from blood cultures and urine in different hospitals in Norway during 2014. An additional aim was to determine the carriage rate of K. pneumoniae, irrespective of resistance, in the Tromsø population. Screening of fecal samples from inhabitants in the Tromsø municipality, showed the carriage rate of ESBL-producing E. coli and K. pneumoniae to be 3.2%. We also found the carriage prevalence of K. pneumoniae, irrespective of resistance, to be 14.7%. Whole-genome sequencing (WGS), was used to determine the population structure of the ESBL-producing carrier strains and the ESBL-producing clinical strains. The genotypic characterization of the ESBL-producing E. coli isolates showed both the carrier strains and the clinical strains were dominated by ST131, with CTX-M-15 as the most prevalent ESBL. Genotypic characterization of the clinical K. pneumoniae strains, showed a dominance by ST307, also with CTX-M-15 as the most prevalent ESBL. Our results show the carriage rate ...